Older adults' preferred and perceived roles in decision-making about palliative chemotherapy, decision priorities and information preferences. Issue 4 (May 2020) - Moth, Erin B.; Kiely, Belinda E.; Martin, Andrew; Naganathan, Vasi; Della-Fiorentina, Stephen; Honeyball, Florian; Zielinski, Rob; Steer, Christopher; Mandaliya, Hiren; Ragunathan, Abiramy; Blinman, Prunella
Abstract: Aim: Patients with cancer have varied preferences for involvement in decision-making. We sought older adults' preferred and perceived roles in decision-making about palliative chemotherapy; priorities; and information received and desired. Methods: Patients ≥65y who had made a decision about palliative chemotherapy with an oncologist completed a written questionnaire. Preferred and perceived decision-making roles were assessed by the Control Preferences Scale. Wilcoxon rank-sum tests evaluated associations with preferred role. Factors important in decision-making were rated and ranked, and receipt of, and desire for information was described. Results: Characteristics of the 179 respondents: median age 74y, male (64%), having chemotherapy (83%), vulnerable (Vulnerable Elders Survey-13 score ≥ 3) (52%). Preferred decision-making roles ( n  = 173) were active in 39%, collaborative in 27%, and passive in 35%. Perceived decision-making roles ( n  = 172) were active in 42%, collaborative in 22%, and passive in 36% and matched the preferred role for 63% of patients. Associated with preference for an active role: being single/widowed ( p  = .004, OR = 1.49), having declined chemotherapy ( p  = .02, OR = 2.00). Ranked most important ( n  = 159) were "doing everything possible" (30%), "my doctor's recommendation" (26%), "my quality of life" (20%), and "living longer" (15%). A minority expected chemotherapy to cure their cancer (14%). Most had discussed expectations of cure (70%), side effects (88%) and benefits (82%) of chemotherapy. Fewer had received quantitative prognostic information (49%) than desired this information (67%). Conclusion: Older adults exhibited a range of preferences for involvement in decision-making about palliative chemotherapy. Oncologists should seek patients' decision-making preferences, priorities, and information needs when discussing palliative chemotherapy.